Microwave Absorbing properties of metal functionalized-CNT-polymer composite for stealth applications - Tahir Abdulrehman (8697696) (2020)
In this study, we report on the electrical properties of multi-wall carbon nanotubes (MWCNT) composites functionalized with metal or metal alloy oxides and embedded in a polyurethane matrix to develop a lightweight material for microwave absorption and shielding. The CNT nanoparticles are functionalized with metallic oxides such as Cobalt oxide, Iron oxide, and Cobalt Iron oxide, at three different concentrations. Metallic oxides are used at 5%, 10%, and 20% concentration of the total CNT percentage weight. The resulting functionalized CNT is mixed with polyurethane polymer at 5% wt of the total composite weight. Three sets of cylindrical samples are developed, and each set contains three different metal oxide concentrations. The dielectric properties of the nine developed samples are obtained by measuring their permittivity spectra using an open-ended coaxial probe technique in the spectral range 5–50 GHz. The absorption efficiency of the composites is then obtained by calculating the reflection loss at normal incidence. The results show that the spectral range of absorption can be tuned by changing the CNT concentration, and the material thickness. Functionalized CNT with different alloyed metal oxides enhanced the absorption efficiency of the polyurethane/CNT composites. Such functionalized composites can be used to replace the common heavyweight materials used for microwave applications. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-020-72928-1